Transformational Leadership’s Influence on Human Resource Performance via Organizational Climate and Commitment - Tovan; Armawati; Mutmainah; Salma D (Jurnal Economic Resource, 2022)
This study aims to examine the impact of transformational leadership on human resource performance through organizational climate and organizational commitment in the Morowali Regency Government, using a sample of 77 respondents and data collected through questionnaires and analyzed using PLS (Partial Least Square) software. The findings of this study indicate that there is a significant influence of transformational leadership on organizational climate and organizational commitment and that organizational climate has a significant influence on employee performance. At the same time, organizational commitment had no significant effect on employee performance in the Morowali Regency Government.